Influence of Process Operation on the Production of Exopolysaccharides in Arthrospira platensis and Chlamydomonas asymmetrica - Jung, Sun-Hwa; Zell, Niklas; Boßle, Fabian; Teipel, Ulrich; Rauh, Cornelia; McHardy, Christopher; Lindenberger, Christoph (Frontiers in Sustainable Food Systems, 2022)
Extracellular polysaccharides, or exopolysaccharides are high–molecular weight sugar-based polymers expressed and secreted by many microorganisms. As host organisms, the functions of exopolysaccharides are diverse, ranging from physical protection via biofilm formation, adhesion, and water retention to biological functions that are not entirely understood such as viral attachment inhibition. Industrial applications of exopolysaccharides can be found in food texture modification; for example, utilizing the hydrocolloidal properties of exopolysaccharides for thickening and gelling purposes to improve food quality and texture. Over the last decade, biologically active exopolysaccharides produced by microalgae have received attention for their potential as antiviral, antibacterial and antioxidative compounds and in the applications. However, relatively low yield and productivity are the limiting factors for full-scale industrial application. In this study, the well-known prokaryotic phototrophic microorganism Arthrospira platensis and the comparatively unknown eukaryotic unicellular green alga Chlamydomonas asymmetrica were used to evaluate the influence of different process parameters on exopolysaccharides formation and productivity. In addition to the essential control variables (light and temperature), the influence of operational techniques (batch and turbidostat) were also investigated. Although the two studied algae are differently affected by above parameters. The light intensity was the most influential parameter observed in the study, leading to differences in exopolysaccharides concentrations by a factor of 10, with the highest measured concentration for A. platensis of cEPS = 0.138 g L−1 at 180 μmol m−2 s−1 and for C. asymmetrica of cEPS = 1.2 g L−1 at 1,429 μmol m−2 s−1. In continuous systems, the achieved exopolysaccharides concentrations were low compared to batch process, however, slightly higher productivities were reached. Regardless of all screened process parameters, C. asymmetrica is the better organism in terms of exopolysaccharides concentrations and productivity.